2021
DOI: 10.1371/journal.pone.0254563
|View full text |Cite
|
Sign up to set email alerts
|

Sero-surveillance for SARS-CoV-2 infection among healthcare providers in four hospitals in Thailand one year after the first community outbreak

Abstract: Background Thailand was the first country outside China to report SARS-CoV-2 infected cases. Since the detection of the first imported case on January 12th, 2020 to the time this report was written, Thailand experienced two waves of community outbreaks (March-April 2020 and December 2020-March 2021). We examined prevalence of SARS-CoV-2 seropositivity among healthcare providers (HCPs) in four hospitals approximately one year after SARS-CoV-2 first detected in Thailand. By March 2021, these hospitals have treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Nevertheless, only one participant could be confirmed by Euroimmune® ELISA, resulting in a seroprevalence of 0.015% [ 20 ]. Furthermore, the serosurveillance of 600 health care providers from 4 hospitals for one year after the first case was detected in Thailand yielded only one seropositive participant (seroprevalence 0.2%) [ 21 ]. Notably, this individual was positive for IgG antibodies against the S protein but not IgG antibodies against the N protein, as determined by Euroimmune® ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, only one participant could be confirmed by Euroimmune® ELISA, resulting in a seroprevalence of 0.015% [ 20 ]. Furthermore, the serosurveillance of 600 health care providers from 4 hospitals for one year after the first case was detected in Thailand yielded only one seropositive participant (seroprevalence 0.2%) [ 21 ]. Notably, this individual was positive for IgG antibodies against the S protein but not IgG antibodies against the N protein, as determined by Euroimmune® ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these cohorts are also examining COVID-19 vaccine effectiveness to SARS-CoV-2 variants by dosing schedules. In Thailand, the Ministry of Health and Influenza Division field staff leveraged close partnerships with academic institutions and hospitals to conduct a serosurvey among health care personnel 1 year after the start of the pandemic ( 32 ) and after COVID-19 vaccination ( 33 ). The 13-country PAHO Network for the Evaluation of Vaccine Effectiveness in Latin America and the Caribbean, known as REVELAC-I for its acronym in Spanish ( 34 ), was activated to assess COVID-19 vaccine effectiveness among hospitalized persons in countries such as Paraguay ( 35 ); CDC supported this work with financial and technical resources.…”
Section: Expansion Of Existing Influenza Evaluation Projects To Inclu...mentioning
confidence: 99%
“…A study among non-healthcare workers with a high potential of exposure to SARS-CoV-2 in the northern regions (the Chiang Mai and Lamphun provinces) during the second wave of the outbreak (November 2020-January 2021) reported 0.9% (n = 1651) positive results for antibody tests [10]. Another study in healthcare workers in the Bangkok metropolitan area, and the western and eastern regions of Thailand from January to March 2021 reported that the positive rate for SARS-Cov-2 IgG-spike antibodies was 0.2% (n = 600) [11]. However, no data from serological survey studies conducted after the outbreak of the fourth wave in Thailand are available, while several countries reported various prevalence rates of COVID-19 seropositivity after the delta outbreak.…”
Section: Introductionmentioning
confidence: 99%